Flux cored arc welding – determination and reduction of fume emission rates. Issue 4 (3rd June 2021) - Hoefer, Kevin; Kusch, Mario
ABSTRACT: The lowering of the German occupational exposure limit from 3 mg/m 3 to 1.25 mg/m 3 by 2018 and the high health hazard from tubular cored electrodes shows the need to determine and minimize the emission potential of such wires. With the background knowledge that 95 % of the emitted welding fumes are caused by the filler metal, the possibility to reduce the emission potential at the source of origin is the best opportunity. The objective of the described research project was to reduce the fumes emitted by tubular cored wires without decreasing their economic benefits. Customary cored wires were investigated as well as design features of the wires were detected to optimize them. The selection and adaptation of the filler metal was carried out in cooperation with the manufacturers within their specifications. The technology and basis for the determination of the fume emission rates forms the DIN EN ISO 15011–1:2017. As a first step, the influence of the wire geometry and the filling type was investigated. Two exemplary results are that metal powder electrodes produced three times higher emission rates than rutile cored wires and that the wire geometry has an influence of 40 % on the emission potential. Afterwards, selected tubular cored wires were studied with the objective to figure out the influence of various process parameters. Such as arc voltage, contact tip work distance and shielding gas composition. One result was that the metal-cored wire responded with the highest changes in emission potential when the welding parameter changed. The investigation showed that the health hazard of tubular cored wires is dependent on their design and the process characteristics. Therefore, the hazard classifications of cored wires, e.g. the German TRGS 528 should be rethought. Furthermore, a good comparison of emission rates from different authors without a defined filter type is very difficult.